Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1242/jcs.180612
|View full text |Cite
|
Sign up to set email alerts
|

Applied stretch initiates directional invasion via the action of Rap1 GTPase as a tension sensor

Abstract: Although it is known that a stiffening of the stroma and the rearrangement of collagen fibers within the extracellular matrix facilitate the movement of tumor cells away from the primary lesion, the underlying mechanisms responsible are not fully understood. We now show that this invasion, which can be initiated by applying tensional loads to a three-dimensional collagen gel matrix in culture, is dependent on the Rap1 GTPases (Rap1a and Rap1b, referred to collectively as Rap1). Under these conditions Rap1 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…We found that both focal adhesion area and length increased in response to strain, and that this increment is bigger than the mere increase due to the mechanical stretching of the substrate on which the cells are cultured. The growth of focal adhesions size induced by different mechanical strains was previously shown either in response to global stimuli like shear stress 24 , uniaxial 11 , 25 or equibiaxial 25 stretching (here in terms of fluorescently labeled adhesion proteins total intensity) or using substrates with modulated rigidity 23 ; as well as in response to locally applied forces 26 , 27 . A key advantage in our experiments lies in the possibility of imaging the same cell at increasing equibiaxial stretching.…”
Section: Resultsmentioning
confidence: 97%
“…We found that both focal adhesion area and length increased in response to strain, and that this increment is bigger than the mere increase due to the mechanical stretching of the substrate on which the cells are cultured. The growth of focal adhesions size induced by different mechanical strains was previously shown either in response to global stimuli like shear stress 24 , uniaxial 11 , 25 or equibiaxial 25 stretching (here in terms of fluorescently labeled adhesion proteins total intensity) or using substrates with modulated rigidity 23 ; as well as in response to locally applied forces 26 , 27 . A key advantage in our experiments lies in the possibility of imaging the same cell at increasing equibiaxial stretching.…”
Section: Resultsmentioning
confidence: 97%
“…MSCs (1.6×10 2 cells/mm 2 ) seeded in microchannels (µ-Slide VI 0.4 ; Ibidi, Munich, Germany) were incubated with or without 10 µM NSC23766 for 24 h. Cells were fixed with formalin (10% neutral-buffered; Sigma) for 30 min, permeabilised with 0.5% Triton X-100 (Sigma) diluted in PBS for 10 min and blocked for 1 h with 1% bovine serum albumin and 10% goat serum (both from Vector Laboratories) or 10% normal horse serum (NHS). Cells were incubated with anti-human podoplanin antibody [5 µg/ml; clone NZ-1.3; batch 4308851 (Mizoguchi et al, 2018)], followed by goat Alexa Fluor 647-conjugated anti-rat-IgG antibody [10 µg/ml; A21247; batch 1834715; Invitrogen, Paisley, UK (Freeman et al, 2017)] or donkey Alexa Fluor 647-conjugated anti-rat-IgG antibody [1:500; 712-606-153; batch 129952; Jackson ImmunoResearch (Mizoguchi et al, 2018)] for 1 h each. Samples were counterstained with Alexa Fluor 488-conjugated phalloidin (16.5 nM) for 30 min and mounted in ProLong Gold Antifade Mountant containing DAPI (both from Thermo-Fisher) or ProLong Diamond Antifade Mountant (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that integrin activation plays a central role during phagocytosis (40,(83)(84)(85)(86), since most phagocytic receptors embody members of the integrin family. Indeed, Freeman and colleagues demonstrated in an elegant piece of work how integrin activation leads to the formation of a diffusion barrier around the opsonized target, which facilitates coordinated particle engulfment during Fc gamma receptor-initiated phagocytosis (87). Interestingly, another recent study using Arp2 knockout cells identified a critical role for Arp2/3 complex-mediated actin assembly in integrin activation, affecting all integrin-dependent processes in macrophages, including migration, adhesion and phagocytosis (75).…”
Section: Fc Gamma Receptor (Fc R)-induced Phagocytosis Is Mainly Accomentioning
confidence: 99%